Lower serum clusterin levels in patients with erosive hand osteoarthritis are associated with more pain - Tereza Kropáčková (BMC Musculoskeletal Disorders, 2018)
Abstract Background The aims of this study were to analyse the serum concentrations of clusterin (CLU) in patients with hand osteoarthritis (OA) and in healthy controls, to compare CLU levels between patients with erosive and non-erosive disease, and to examine the association of CLU levels with clinical and laboratory parameters. Methods A total of 135 patients with hand OA (81 with erosive and 54 with non-erosive disease) and 53 healthy individuals were included in this study. All patients underwent clinical and hand joint ultrasound examination. The Australian/Canadian (AUSCAN) hand osteoarthritis index, algofunctional index and a visual analogue scale (VAS) for the measurement of pain were assessed. Serum levels of CLU were measured by an enzyme-linked immunosorbent assay (ELISA). Results Serum levels of CLU were significantly lower in patients with hand OA than in control subjects (p < 0.0001). In addition, patients with erosive hand OA had significantly lower CLU levels than those with non-erosive disease (p = 0.044). Negative correlations between CLU levels and pain as assessed by the AUSCAN score and the VAS were found in patients with erosive hand OA (r = − 0.275; p = 0.013 and r = − 0.220; p = 0.049, respectively). Conclusion The present study demonstrates that lower concentrations of CLU are found in hand OA patients than in healthy individuals, especially in those with erosive disease, and that CLU concentrations have a negative association with hand pain.